2016
DOI: 10.1016/j.joca.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between disease-related pain and cortisol levels in women with osteoarthritis

Abstract: Objectives To determine if 1) Osteoarthritis (OA)-related pain is associated with the diurnal cortisol pattern and cortisol levels; 2) the diurnal pattern of cortisol varies with severity of OA pain and 3) the association between OA pain and cortisol is mediated by daily experience variables (DEV). Design In a community-based study of changes in regional and widespread pain among women with OA, participants (n=31) completed daily diaries and collected three saliva samples daily for 7 days. Severity of OA-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This finding may explain why weight loss may be directly associated with pain level 28 and that the strategic approach to decrease pain could allow individuals to do more exercise. A recent study showed that in women with OA, disease-related pain was positively associated with cortisol production, particularly with greater pain intensity 29 . Pain is a potential stressor and activator of the hypothalamic-pituitary-adrenal axis, which has been related to increased visceral obesity 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding may explain why weight loss may be directly associated with pain level 28 and that the strategic approach to decrease pain could allow individuals to do more exercise. A recent study showed that in women with OA, disease-related pain was positively associated with cortisol production, particularly with greater pain intensity 29 . Pain is a potential stressor and activator of the hypothalamic-pituitary-adrenal axis, which has been related to increased visceral obesity 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Pain has been associated with elevations in cortisol and increased cortisol exposure [3]. When examining the correlation between the change in pain level and the relative percentage change in cortisol no significant correlation was found ( Figure 4A).…”
Section: Reported Changes In Pain (Vas) Did Not Correlate With Changementioning
confidence: 96%
“…Pain, as a result of inflammation and degeneration, is a significant symptom of OA. In response to pain, the stress-axis is activated, resulting in increased circulating cortisol levels [3]. Over time, chronic pain associated stress can lead to cortisol dysfunction and widespread inflammation, thus exacerbating inflammationassociated joint degeneration [4].…”
Section: Introductionmentioning
confidence: 99%
“…Results from two studies suggest possible gender related differences in cortisol and pain associations, which has been reported in other non-OA related stress studies. 249 Carlesso et al 250 found that pain was positively associated with increased saliva cortisol levels throughout the day in female OA patients. In this study however, cortisol levels upon awakening were not measured and this would have provided a better indication whether the diurnal pattern of cortisol secretion was also disrupted in these OA patients.…”
Section: Endogenous Glucocorticoidsmentioning
confidence: 99%